Numerical Simulation of 3-D Internal Crack Propagation in Rock under Semi-circle Bending - Zhang, Zhitao; Gu, Weijie (Periodica Polytechnica Civil Engineering, 2022)
Semi-circle bending (SCB) test is an important test in the field of rock fracture. In order to investigate the propagation process of 3-D internal cracks under semi-circular bending, numerical simulations of SCB specimens were carried out based on the finite element method and adaptive mesh technique. The results show that the numerical simulation results of this method are in good agreement with the previous laboratory test. The symmetrical loading model belongs to the pure I loading where the value of KI is positively related to the bottom load span S/R. The asymmetric loading model belongs to mix-mode loading. With the increase of unilateral load span S2/R, there is a decline and then a rise of the value of SIF at the same point at the crack tip. The S2/R is an important factor affecting the mechanical properties of rock specimens. The crack propagation path was obtained based on the maximum tensile stress (MTS) criterion. In-plane propagation of the internal crack in the symmetrically loading model leads to failure of the specimen. Wing propagation of the internal crack in the asymmetrically loading model causes the specimen to fracture into two asymmetrical parts. Quantitative analysis of the internal crack propagation of the symmetrical loading model shows that the growth rate of the lower end of the crack is the largest, and the upper end of the crack is the smallest. The above results can provide a reference for the research on the propagation of 3-D internal cracks of SCB specimens.